Tinjauan Yuridis Terhadap Putusan Hakim Dalam KasusTindak Pidana Pencurian Yang Dilakukan Oleh Anak(Studi kasus Putusan Pidana Nomor: 2/PID.SUS-Anak/2014/PN.Kln) - Ardianto, Feri, Hartanto, S.H., M.Hum, Bambang Sukoco S.H.,M.H (2016)
The purpose of this study to know the implementation of elements of Section 363 subsection (1) 4th Criminal Code on criminal offenses of theft with the circumstances aggravating done by children and to know the basic legal considerations the judge in deciding the criminal case of theft with the circumstances aggravating done by children, The method used is descriptive-analytic, with normative juridical approach. The data source consists of primary data and secondary data including primary legal materials, secondary, tertiary. Data were collected by literature study, then analyzed by qualitative analysis. The results of this study indicate that the application of material criminal law against theft by state burdensome, namely Article 363 paragraph (1) 4th Criminal Code in accordance with the facts of the law, both the statements of witnesses, expert testimonies and information from the defendant, only in the application of sanctions the principle of restorative justice here is not used by the judge, so it is not in accordance with Article 5 (1) of Law Number 11 Year 2012 on Child Criminal Justice System. While the basic legal consideration of judges in deciding the case based on Article 193 paragraph (2) b in conjunction with Article 21 paragraph (4) Criminal Procedure Code, Article 194 Criminal Procedure Code and Article 22 paragraph (4) Criminal Procedure Code.